Scleritis Caused by In Vitro Linezolid-Resistant Nocardia asteroides - Andres Gonzalez; Kaihan Fakhar; David Gubernick; Sonal Tuli (Case Reports in Ophthalmological Medicine)
Purpose. To describe a case of postoperative scleritis caused by a novel strain of Nocardia resistant to linezolid and trimethoprim-sulfamethoxazole (TMP-SMX). Methods. Case report of a patient with microbiologically proven scleritis due to Nocardia asteroides. Results. The patient presented with pain, redness, and nodules on the sclera three months following pterygium excision with mitomycin C and amniotic membrane placement. As no response was noted with empiric treatment for bacterial scleritis, debridement was performed. The cytopathology report showed gram positive filamentous bacteria. A presumptive diagnosis of Nocardia scleritis was made and therapy was initiated based on a literature review on treatments for Nocardia infections. Cultures returned growing Nocardia asteroides. Antibiotic sensitivity testing revealed resistance to linezolid and TMP-SMX which are the traditional drugs of choice for Nocardia. The patient was treated with amikacin and imipenem as well as extensive debridement with pedicle grafts. The patient’s scleritis resolved with a good visual outcome. Conclusions. Cultures should be obtained in all cases of necrotizing scleritis in patients with a recent history of conjunctival surgery to rule out unusual organisms such as Nocardia. Although literature states that resistance to linezolid and TMP-SMX is rare in Nocardia, sensitivity testing can be useful in unresponsive cases.